Halide–propene complexes: validated DSD-PBEP86-D3BJ calculations and photoelectron spectroscopy. Issue 42 (24th October 2022) - Watson, Peter D.; Corkish, Timothy R.; Haakansson, Christian T.; McKinley, Allan J.; Wild, Duncan A.
Abstract : Anion photoelectron spectroscopy has been used to determine the electron binding energies of the X − ⋯C3 H6 (X = Cl, Br, I) complexes. Abstract : Anion photoelectron spectroscopy has been used to determine the electron binding energies of the X − ⋯C3 H6 (X = Cl, Br, I) complexes. To complement the experimental spectra the DSD-PBEP86-D3BJ functional has been employed, following comparison with previously calculated halide/halogen-molecule van der Waals complexes. To validate the functional, comparison between the complex geometries and vertical detachment energies with both experimental and CCSD(T)/CBS data for a suite of halide–molecule complexes is also made. PES spectra determine the electron binding energies as 3.89 eV and 4.00 eV, 3.59 eV and 4.01 eV, and 3.26 eV and 4.20 eV for transitions to perturbed 2 P states of the chlorine, bromine and iodine complexes respectively. Two contributing structures resulting in the photoelectron spectrum are those where the halide is coordinated by two hydrogens, each from a terminal carbon in C3 H6, and when bifurcating the CC bond. These complexes are distinct from the corresponding halide–ethene complexes and represent potential entry pathways to haloakyl radical formation in atmospheric and extraterrestrial environments.